Factors Associated with Engaging in Bystander Intervention Behavior Among College Students - Bloom, Brittnie E. (Journal of interpersonal violence, 2024)
Sexual violence (SV) is a well-documented and highly prevalent issue on college campuses that disproportionately impacts women, students of color, and students who identify as lesbian, gay, bisexual, transgender, queer (LGBTQ). In recent years, bystander intervention programming has emerged as a promising prevention strategy for colleges due to its success in preventing SV before it occurs using community involvement; however, little consideration has been given to the power, status, or position that a bystander has when deciding whether to intervene and weighing the potential consequences of their actions. In order to inform university campus bystander intervention programming and increase its effectiveness, more work is needed to understand specific student characteristics (e.g., race/ethnicity, gender identity, sexual orientation, history of SV) that may be associated with engaging in bystander behavior in SV risk situations. Using cross-sectional data from a large west-coast university, 592 students were surveyed about their SV-related experiences. Poisson regression models were utilized to determine the relative risk of engaging in bystander behavior by sociodemographic identities and history of SV victimization. Our fully adjusted model indicated that experiencing attempted and completed sexual assault was associated with engaging in bystander behavior; belonging to specific minority groups was differentially associated with engaging in bystander behavior, as was belonging to a minority group and having a history of SV. Personal histories, identities, and power inequity matter when deciding to engage in bystander behavior. Additional research is needed to create more well-rounded and population-specific bystander intervention programs that are inclusive of diverse student voices and experiences.